ANALISIS PENERAPAN BALANCE SCORECARD SEBAGAI ALTERNATIF PENGUKURAN KINERJA DI UNIVERSITAS TRIDINANTI PALEMBANG - Dwi Septa Aryani (JURNAL KOMPETITIF, 2016)
University of Tridinanti Palembang (UTP) is one of a private university in Palembang. In which during the improvement has been getting rise and down. As related on it, this research was discussed how UTPâ€™s performance if be measured by implementing four perspectives balance scorecard. The aim of this research was to analyze prospect of financial, customer, internal business process, also developing and learning at UTPThe result showed as : first, be seen from financial perspective, performance UTP output was good. It can be seen by covering budget of performance income. Second, performace of customer perspective was good assesment, because respondents have got satisfy and trust with the service had given. Third, the performance of internal business process was good by seeing academic performance even though performance of administration department also good. Fourth, developing and learning performance were good, UTP has been getting commitment to give scholarship for lecturers but rarely involved lecturers and staffs in deciding process.Application in this research was hoped in order to UTP able to implement balance scorecard in assesing performance in the future. By implementing it, can be helped to gain decisions and policies. Keywords: balance scorecard, performance measurement